Abraham Lincoln and the Second American Revolution. - McPherson, James M. (Oxford University Press, USA, 1991)
James McPherson has emerged as one of America's finest historians. Battle Cry of Freedom, his Pulitzer Prize-winning account of the Civil War, was a national bestseller that Hugh Brogan, in The New York Times Book Review, called ""history writing of the highest order."" In that volume, McPherson gathered in the broad sweep of events, the political, social, and cultural forces at work during the Civil War era. Now, in Abraham Lincoln and the Second American Revolution, he offers a series of thoughtful and engaging essays on aspects of Lincoln and the war that have rarely been discussed in depth.